(untitled) (Vietnam Journal of Community Medicine, 2022)
Infertility tends to increase, there have been numerous studies on the causes of infertility such as age, gynecological diseases, and genetic causes... however, the influence of lifestyle on fertility is still little known. The purpose of this report is to provide an overview of several lifestyle behaviors that affect fertility. Methods used are reviewing studies on a number of lifestyle behaviors that affect reproductive capability. Conclusion & recommendations: In planning for pregnancy, couples should quit smoking, try to maintain a BMI of 18.5 - 25 kg/ m2, should exercise, but not more than 5 hours/week; Women who are planning to become pregnant, are pregnant should avoid alcoholic beverages, because the level of safe alcohol consumption for the fetus has not been determined, limit caffeine consumption.